The developmental origins of adult disease - Gluckman, Peter D. (Matern Child Nutr, 2005)
Epidemiological and clinical observations have led to the hypothesis that the risk of developing some chronic diseases in adulthood is influenced not only by genetic and adult lifestyle factors, but also by environmental factors acting in early life. These factors act through the processes of developmental plasticity and possibly epigenetic modification, and can be distinguished from developmental disruption. The concept of predictive adaptation has been developed to explain the relationship between early life events and the risk of later disease. At its base, the model suggests that a mismatch between fetal expectation of its postnatal environment and actual postnatal environment contribute to later adult disease risk. This mismatch is exacerbated, in part, by the phenomenon of ‘maternal constraint’ on fetal growth, which implicitly provides an upper limit of postnatal nutritional environment that humans have adapted for and is now frequently exceeded. These experimental, clinical and conceptual considerations have important implications for prevention and intervention in the current epidemic of childhood obesity and adult metabolic and cardiovascular disorders.